TUMBUHAN SUMBER PANGAN YANG DIMANFAATKAN OLEH MASYARAKAT SEKITAR HUTAN TEMBAWANG DESA NANGA KOMPI KECAMATAN NANGA SAYAN KABUPATEN MELAWI - Dasman, Yusuf; mahi, Ora; Sisillia, Lolyta (Universitas Tanjungpura, 2015)
The research aims to determine the types of plants food sources available and used by communities in Tembawang forest Nanga Sayan subdistrictÂ Melawi District. The benefits of this research can provide information about food sources and utilization of plant communities that exist around the village of Nanga Kompi, as well as the basis for management and development of the region by the agencies involved in the protection, conservation and utilization of plant food resources in the future. This study uses snowball sampling technique or performed in sequence by asking for information on people who have been interviewed or contacted prior to interview, observation, and literature study. Based on the results of the study found as many as 92 plants classified to 45 famili. Most is family Arecaceae and Anacardiaceae 6 species (6.52%). Parts used are part of the fruit that is as much as 67 species (72.83%). How to use it by way of direct consumption 41 species (45%), processing methods with cooked 35 species (38%), the most widely used is derived from the group of fruits that 52 species (56.52%), vegetables 38 species (41.30%), as much as 55 species (59.78%) is a wild plant. Keywords : food plants, Nanga Kompi village, tembawang forest